Atividade de estudo como fundamento do desenvolvimento do pensamento teórico de crianças em idade escolar inicial - Clarindo, Cleber Barbosa da Silva [UNESP] (2015)
Dissertation presented to the Program of Postgraduate Education Program in the Faculty of Philosophy and Sciences, Universidade Estadual Paulista - UNESP - Marília, aims to understand and show how learning activity, through its content, the theoretical knowledge, enables the major changes in the way the school children understand and analyze the world of phenomena, relations and human assets. This formulation is due to the realization that learning activity, understood by theorists of Cultural-Historical Theory as the main activity of the school children, has a great importance in the formation of intellectual and cognitive strengths of these children in the early years of elementary school, because it develops in them a theoretical relationship toward the world. By means of the theoretical knowledge new capabilities are developed in the subjects, that enable them develop of a new form of action to realize their relation with the human world. Such understanding contrasts with the reality of our public schools which, as a rule, have failed to develop these skills in students. We hypothesized that the learning activity is a suitable option for the development of pedagogical work that aims to develop in the students higher psychological new formations that allow the appropriation of the most elaborate contents existing in human culture and, with it, a new way to think and act in the environment where they live. This study is characterized as a theoretical one; for its development actions were realized to locate, gather and analyze theories contained in publications, texts, articles and books by authors from Cultural-Historical Theory that discuss the issues focused on learning activity, theoretical thinking and the role of the teaching process in children development. In this context our research has as its main result the finding that school children have historically cognitive reserves to appropriate forms of theoretical...